The Role of Good School Environment on the Quality of School Activities in Qatif Zone Schools - Alobaidan, Safiah Saeed Ali; Alghazo, Ali (Journal of Educational and Psychological Sciences, 2019)
The current study aimed to explore the relationship between the well prepared school environment and the quality of schools activities that are directed to students’ benefits. This study follows the mixed methods design that combines both quantitative and qualitative data collection and analysis. The research tools that are used in this study is a closed-ended e-survey for school activity leaders and interviews with 5 supervisors. The non-random pilot of this research consists of (23) school activity leaders from elementary, intermediate and secondary schools and (5) supervisors in Qatif zone. The research findings pointed out the real effective well-prepared school environment role on the good quality outcomes of school activities in Qatif Area, and that most schools lack the application of quality in school activities. This research will shed light on how effective is the well prepared school environment to enrich the kinds and the effectiveness of school activities according to the quality standards of the Ministry. This emphasizes the role of the Ministry of Education to exert more efforts to prepare schools with required facilities and equipment to facilitate the quality of school activities.